2011
DOI: 10.1177/0145445511427973
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Error-Correction Strategies in Discrete Trial Training

Abstract: Error-correction strategies are essential considerations for behavior analysts implementing discrete trial training with children with autism. The research literature, however, is still lacking in the number of studies that compare and evaluate error-correction procedures. The purpose of this study was to compare two error-correction strategies: Independent Probe and Delay across learners with autism in an intensive intervention program. Two studies were conducted. The first study compared the two procedures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 8 publications
3
17
1
Order By: Relevance
“…These findings are consistent with other studies showing the effectiveness of procedures that require multiple responses from students following errors, a strategy that is often called positive practice or directed rehearsal (e.g., Foxx & Jones, 1978, Ollendick, Matson, Esveldt-Dawson, & Shapiro, 1980. Turan et al (2012), who also obtained inconsistent results across subjects when comparing two commonly recommended error-correction procedures for discrete-trial teaching, suggested that instruction should be individualized across learners. Smith et al (2006) compared three conditions that involved providing a different response following errors: (a) no consequences, (b) vocal feedback only (saying "no"), and (c) a model of the correct response.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with other studies showing the effectiveness of procedures that require multiple responses from students following errors, a strategy that is often called positive practice or directed rehearsal (e.g., Foxx & Jones, 1978, Ollendick, Matson, Esveldt-Dawson, & Shapiro, 1980. Turan et al (2012), who also obtained inconsistent results across subjects when comparing two commonly recommended error-correction procedures for discrete-trial teaching, suggested that instruction should be individualized across learners. Smith et al (2006) compared three conditions that involved providing a different response following errors: (a) no consequences, (b) vocal feedback only (saying "no"), and (c) a model of the correct response.…”
supporting
confidence: 90%
“…All six students acquired more words assigned to the ASR condition than to the NR condition. Results of other studies on different errorcorrection procedures have been less consistent (Rodgers & Iwata, 1991;Smith et al, 2006;Turan, Moroz, & Croteau, 2012). Results of a subsequent evaluation, in which the experimenter required subjects to repeat either the targeted word or a nontargeted word contingent on errors, indicated that the multiple-response repetition error-correction procedure functioned as punishment for incorrect responding.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Some authors have suggested that therapists should insert a known (i.e., previously acquired) target between a prompted response and an opportunity for an independent response when they implement error‐correction procedures (e.g., Bondy & Frost, ; Turan, Moroz, & Croteau, ). However, in most studies on this error‐correction method, the therapist delivered a prompt after an incorrect response and then immediately set up the occasion for the individual to respond independently (e.g., by delivering the S D again with no prompt).…”
mentioning
confidence: 99%
“…A variety of skills were targeted in these three studies, including requesting through picture selection (Carr & Felce, 2008), sight-word reading (Marvin et al, 2010), receptive selection, and labeling (Turan et al, 2012). The error-correction procedures used in the studies varied significantly.…”
Section: Discussionmentioning
confidence: 99%